2023
DOI: 10.3390/ijerph20021289
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability of the Functional Electromechanical Dynamometer for Squat Exercise

Abstract: Background: the main objective of this study was to evaluate the test-retest reliability of two different functional electromechanical dynamometry (FEMD)-controlled squat training protocols. Methods: twenty-eight healthy young adults volunteered to participate in this study. They attended the laboratory on four different days and performed four sessions: two of three sets of 12 repetitions at 75% 1RM and two of three sets of 30 repetitions at 50% 1RM. The range of movement (ROM), mean dynamic strength (MDS), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…In the study by Baena-Raya et al [16], they analyzed the reliability of mid-thigh traction kinetic variables with FEMD, reporting that the device has a high absolute reliability (CV = 2.26-2.51%) and an extremely high relative reliability in the evaluation of peak force (ICC = 0.94-0.95). In another study, del-Cuerpo et al [13] obtained similar results to those of this study. In their study, they evaluated two different FEMD controlled squat training protocols in a group of healthy young adults, reporting a null effect size (ES = 0.07-0.17), an acceptable absolute reliability for the protocols used (CV < 10%) for all variables, and an almost perfect relative reliability (ICC = 0.91-1.00).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the study by Baena-Raya et al [16], they analyzed the reliability of mid-thigh traction kinetic variables with FEMD, reporting that the device has a high absolute reliability (CV = 2.26-2.51%) and an extremely high relative reliability in the evaluation of peak force (ICC = 0.94-0.95). In another study, del-Cuerpo et al [13] obtained similar results to those of this study. In their study, they evaluated two different FEMD controlled squat training protocols in a group of healthy young adults, reporting a null effect size (ES = 0.07-0.17), an acceptable absolute reliability for the protocols used (CV < 10%) for all variables, and an almost perfect relative reliability (ICC = 0.91-1.00).…”
Section: Discussionsupporting
confidence: 90%
“…It is crucial to employ evaluations that can distinguish between different types of analytical advancements in force creation when measuring force [11]. When it comes to training and assessing the kinetic variables of power, speed, and strength of various human movements [12], as well as the various forms of muscular contraction and strength manifestations in free, mono-, or multi-joint movement of the entire body [13], functional electromechanical dynamometry (FEMD) is a perfect tool. When compared to the gold standard, or the isokinetic device, the FEMD is especially easy to use and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…The order of the exercises was randomized, and they were given five minutes of rest between each set. The test-retest reliability of the FEMD for squat exercise was demonstrated in a previous study [32]. The protocol of the study is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 64%
“…The individuals showed up for the study in accordance with the directions given by the researcher. When they arrived at the laboratory, as it was done in del-Cuerpo [32], they were fitted with the gas analyzer mask, and the gas analysis started. They remained seated in a relaxed position for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation